Comparison of two rapid test kits with real time polymerase chain reaction for early diagnosis of dengue in Sri Lanka. Issue 2 (4th March 2022) - Ariyaratne, MHJD; Gunasekara, Peshala; Wajirasena, Poornima Hasanthi; Rathnayake, Dilini Malsha; Dilani, Desha; Chathuranga, Teshan; Gomes, Laksiri; Jayatunga, DADL; Wewita, SJC; Meegahage, Thilini; Jayasinghearachchi, Himali S.; Wijewickrama, Ananda; et al.
ABSTRACT: Dengue is among the deadliest insect-borne diseases circulating in Sri Lanka. Most of the infections that are diagnosed early are manageable. However, delays in diagnosis may cause fatalities. We evaluated the dengue NS1 antigen card and NS1 SD kit for early diagnosis of dengue using samples from 116 RT-PCR-positive patients admitted within 5 days of the fever onset. RT-PCR tests were performed as standard tests. IgM and IgG ELISA tests were carried out to identify primary and secondary infections. Of the 116 patients who tested positive for dengue using PCR, 48 were positive using NS1 antigen card and 45 were positive using NS1 SD. Patients with 100 copies or higher viral load showed a higher sensitivity in both antigen card and NS1 SD. Of 34 primary infections evaluated, 23 were positive by NS1 antigen card, while the positivity was 21 by NS1 SD. Of the 30 secondary infections evaluated, 15 were positive by NS1 antigen card while 14 by NS1 SD. Our findings showed that while the rapid tests are convenient and much easier to use than PCR, they are less sensitive and need improvement. Until then, clinical diagnosis should have more emphasis on the early diagnosis of dengue.